Chronic Chagas disease with advanced cardiac complications in Japan: Case report and literature review. Issue 5 (October 2015) - Imai, Kazuo; Maeda, Takuya; Sayama, Yusuke; Osa, Morichika; Mikita, Kei; Kurane, Ichiro; Miyahira, Yasushi; Kawana, Akihiko; Miura, Sachio
Abstract Due to the unprecedented recent increases in global migration, Chagas disease has become a global health threat and its epidemiology has drastically changed. Here we describe the first case in Japan of benznidazole treatment for chronic Chagas disease characterized by advanced cardiac complications. A 55-year-old Japanese–Brazilian woman who had previously presented with chronic heart failure was diagnosed as having Chagas disease and treated with benznidazole to prevent aggravation of her cardiac complications. However, benznidazole administration was stopped on day 56 due to severe drug-induced peripheral neuritis. Sixteen months later, her serologic test for Trypanosoma cruzi is still positive and she is being followed regularly by cardiology. Despite an estimated prevalence of over 4000 cases in Japan, only a few cases of Chagas disease have been reported. A Medline search revealed only 7 cases identified between 1995 and 2014 in Japan: in 6 cases, complications of chronic Chagas disease were apparent at the time of presentation, and sudden death occurred in 2 of these cases due to cardiac complications. This clinical case and literature review re-emphasize the urgent need to establish a surveillance network and improve the diagnostic methods and treatment framework for Chagas disease in Japan.